720 Targeting MARCO and IL-37R on anti-inflammatory macrophages in lung cancer blocks regulatory T cells and shift balance to support cytotoxic lymphocyte function. (9th November 2020) - Fleur, Linnéa La; Botling, Johan; He, Fei; Pelicano, Catarina; Palano, Giorgia; Mezheyeuski, Artur; Micke, Patrick; Ravetch, Jeffrey; Karlsson, Mikael; Sarhan, Dhifaf
Abstract : Background: The progression and metastatic capacity of solid tumors are strongly influenced by immune cells in the tumor microenvironment (TME). In non-small cell lung cancer (NSCLC) accumulation of anti-inflammatory tumor-associated macrophages (TAMs) is associated with worse clinical outcome and resistance to therapy. Numerous clinical trials aiming to recover T cell anti-tumor activity have been failing due to the persistence immune suppression in TME. Thus, there is a clinical need for alternative treatments targeting the suppressive function of the TME. We have previously shown that antibodies targeting the scavenger receptor MARCO reprograms the pro-tumoral TAMs in murine cancer models. Here, we investigated the immune landscape of NSCLC in the presence of MARCO expressing TAMs. We tested targeting MARCO or the tumor mechanisms inducing MARCO on human TAMs and hypothesized that targeting these mechanisms will remodel the suppressive environment and relive the anti-tumor responses to increase the efficacy of immunotherapy. Methods: To test our hypothesis, we first investigated the immune landscape of NSCLC in the presence of pro-tumoral MARCO+TAMs compared with tumors infiltrated by MARCO-TAMs. We next used RNAseq to analyze differential gene expression in NSCLC tumors infiltrated by MARCO positive or negative macrophages. In vitro, cytokine differentiated macrophages alternatively cultured with lung cancer cell lines were co-cultured with Natural Killer (NK) cells and T cells to mimic their interaction in the TME. Later, macrophages were treated with targeting antibodies and their phenotype and function were examined prior and following interaction with other immune cells. Results: We found that MARCO expressing TAM numbers correlated with increased occurrence of regulatory T cell and effector T cells and decreased NK cells in NSCLC infiltrated by MARCO+TAMs. Furthermore, transcriptomic data from the tumors uncovered a correlation between MARCO expression and the anti-inflammatory cytokine IL-37. Studies in vitro subsequently showed that lung cancer cells polarized macrophages to express MARCO and gain an anti-inflammatory phenotype through the release of IL-37. These human MARCO expressing TAMs blocked cytotoxic T cell and NK cell activation, inhibiting their proliferation, cytokine production and tumor killing capacity. Mechanistically, MARCO+ macrophages enhanced regulatory T (Treg) cell proliferation and IL-10 production and diminished CD8 T cell activities. Targeting MARCO or IL-37 receptor (IL-37R) repolarized TAMs resulted in recovered cytolytic activity and anti-tumoral capacity of NK cells and T cells. Conclusions: In summary, our data demonstrate a novel immune therapeutic approach targeting human TAM immune suppression of NK and T cell anti-tumor activities and remodel immune suppression. Ethics Approval: The study was approved by Institutional Ethics Board, approval number Dnr 2013.977-31.1.